1986
DOI: 10.1111/j.1550-7408.1986.tb05567.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Endogenous Development of Three Isolates of Cryptosporidium in Suckling Mice1

Abstract: Suckling mice were used as a model host to compare the endogenous development of three different isolates of Cryptosporidium: one from a naturally infected calf, one from an immunocompetent human with a short-term diarrheal illness, and one from a patient with acquired immune deficiency syndrome (AIDS) and persistent, life-threatening, gastrointestinal cryptosporidiosis. After oral inoculation of mice with oocysts, no differences were noted among developmental stages of the three isolates in their sites of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
159
4
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(180 citation statements)
references
References 18 publications
(9 reference statements)
15
159
4
2
Order By: Relevance
“…Although in the last few years we have obtained many ultrastructural images of this Cryptosporidium in cultured MDCK cells (Rosales et al 1993b), chick embryos ) and in calf tissues (Mascaró et al 1993), we have never found, either in sporozoites or in merozoites cuts, micronemes arranged in parallel stacks or in zigzag patterns as so clearly described by other authors (Current & Reese 1986, Liebler et al 1986, Fayer et al 1990, Bonnin et al 1990, Rondanelli et al 1993). In our isolate the micronemes are never orderly (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Although in the last few years we have obtained many ultrastructural images of this Cryptosporidium in cultured MDCK cells (Rosales et al 1993b), chick embryos ) and in calf tissues (Mascaró et al 1993), we have never found, either in sporozoites or in merozoites cuts, micronemes arranged in parallel stacks or in zigzag patterns as so clearly described by other authors (Current & Reese 1986, Liebler et al 1986, Fayer et al 1990, Bonnin et al 1990, Rondanelli et al 1993). In our isolate the micronemes are never orderly (Fig.…”
Section: Resultssupporting
confidence: 51%
“…Our TEM and LM study documented all C. parvum developmental stages on the surface of the tracheal and bronchial epithelial cells without involvement of lung parenchyma (Meulbroek et al, 1991). These forms were morphologically similar to those described in the intestinal lumen (Vetterling et al, 1971;Pohlenz et al, 1978;Goebel & Braendler 1982;Pearson & Logan, 1983;Lefkowitch et al, 1984;Current & Reese, 1986;Meulbroek et al, 1991). Moreover, the epithelium bea ring the parasitic stages from rats sacrificed at the end of the study protocol did not show progressive histo logic changes, with appearance of an immature malpighian metaplasia, as recently reported by others (Roussel et al, 1995).…”
Section: Discussionsupporting
confidence: 75%
“…Vacuolation has also been reported ultrastructurally in Cryptosporidium spp. (Vetterling et al, 1971;Current and Reese, 1986;Lumb et al, 1988;Ostrovska and Paperna, 1990). It is known that the vacuolation occurs as a result of secretion from the micronemes, rhoptries, and dense granules.…”
Section: Discussionmentioning
confidence: 99%